(η4-Trimethylenemethane)(1,1,1-tris{[bis(4-methoxyphenyl)phosphanyl]methyl}ethane)ruthenium(II) diethyl ether hemisolvate - Carolin A. M. Stein; Elisabetta Alberico; Anke Spannenberg; Matthias Beller; Henrik Junge (IUCrData)
The title compound, [Ru(C47H51O6P3)(C4H6)]·0.5C4H10O, consists of an RuII atom coordinated by 1,1,1-tris{[bis(4-methoxyphenyl)phosphanyl]methyl}ethane in κ3-coordination mode and an η4-coordinating trimethylenemethane ligand. The complex molecule is co-crystallized with a diethyl ether solvent molecule. A half diethyl ether molecule was considered, whereas additional disordered solvent molecules were removed from the diffraction data with the SQUEEZE procedure in PLATON [Spek (2015). Acta Cryst. C71, 9–18].